Technical innovation in the art of hyper-realism - Miaad Mosa Hasan (مجلة فنون البصرة, 2024)
In the period following World War II, a postmodern period in which cultural activity increased and the creation of new characteristics and patterns of form in social and economic life and is no longer the old artistic pressure is dominant, but the media, technology and the market and called the community the term consumer or multinational capitalism emerged new movements, including the art of hyperrealism subject of research has included the first chapter of the research problem, which ended with the following question:(what is the property of technical renewal brought by excessive realism)The aim of the study was to know the renewal in the art of hyperrealism and the techniques used in the works of art, the limits of the research included models of the art of hyperrealism for the period(1969/1979) in Europe/ America. The second chapter included two sections, the first dealt with intellectual and cultural transformations and their impact on postmodern arts and the second came on two axes, the first; the points of difference between the original image and the imaginary image and its relationship to the art of hyperrealism, and the second: the artistic characteristics of hyperrealism and its artists. In the third chapter, the research procedures, where the descriptive approach was relied on to analyze the sample taken from the research community, which is a set of works that have been viewed through books and scientific sources and the selection of a sample representing the subject in an intentional manner amounted to 3 drawing works with the use of the observation tool and what was stated in the indicators for analysis. Keywords: renewal, technical, art, realism, excessive.